Desorption characterization of methane and carbon dioxide in coal and its influence on outburst prediction - Yunpei Liang; Fakai Wang; Yongjiang Luo; Qianting Hu (Adsorption Science & Technology)
Coal and gas outburst is a dynamic phenomenon with violent eruptions of coal and gas from the working coal seam. It has been proved that the rapid desorption within a short period is necessary for the occurrence of an outburst. Due to limitation of the present test condition, gas desorption characterization for the first 60 s has not been researched sufficiently. In the present study, an experimental apparatus with the ability of high-frequency data collection was developed. Initial desorption characterization of methane and carbon dioxide in coal was experimentally studied. Both the initial desorption characterization of methane and carbon dioxide were experimentally studied with different equilibrium pressures. The desorbed gas pressure was measured at desorption time phase of 0–10 and 45–60 s, besides the initial amount of desorbed gas and initial diffusion velocity of coal gas were calculated to assess their risk of outburst. The results show that the gas pressure for both methane and carbon dioxide increases sharply in the initial time and then levels off, and the total amount of desorbed gas increases with the increasing desorption time. Although the amount of desorption methane is slightly larger than that of carbon dioxide at the beginning, the total amount of desorbed carbon dioxide is significantly larger than that of methane at the desorption process. Therefore, it can be concluded that the coal and carbon dioxide outburst is more dangerous than the coal and methane outburst based on the obtained experimental results.